Genetic Modification of Brain Organoids - Fischer, Jan; Heide, Michael; Huttner, Wieland B. (Frontiers in Cellular Neuroscience, 2019)
Brain organoids have become increasingly used systems allowing 3D-modeling of human brain development, evolution and disease. To be able to make full use of these modeling systems, researchers have developed a growing toolkit of genetic modification techniques. These techniques can be applied to mature brain organoids or to the preceding embryoid bodies (EBs) and founding cells. This review will describe techniques used for transient and stable genetic modification of brain organoids and discuss their current use and respective advantages and disadvantages. Transient approaches include adeno-associated virus- (AAV) and electroporation-based techniques, whereas stable genetic modification approaches make use of lentivirus (including viral stamping), transposon and CRISPR/Cas9 systems. Finally, an outlook as to likely future developments and applications regarding genetic modifications of brain organoids will be presented.